(untitled) (Journal of Interdisciplinary Insights, 2025)
The Shanghai Cooperation Organisation (SCO), established in 2001, has evolved from a regional security mechanism into a pivotal inter-governmental organization with a global strategic footprint. The 2025 SCO Summit in Tianjin represents a definitive paradigm shift, underscoring the organization’s ambition to actively shape a more multipolar world order. Marked by unprecedented attendance, the summit culminated in the Tianjin Declaration, a document expressing a collective commitment to principles of justice, equality, and mutual respect in international affairs. Key outcomes included the advancement of a Global Governance Initiative and a decisive push to establish an SCO Development Bank. These initiatives directly challenge the existing, Western-dominated international financial and political architecture, aiming to provide alternatives for developing nations. The summit, therefore, signifies the SCO’s transition from a forum for regional consultation to a proactive coalition advocating for substantive structural reform in global governance, accelerating the transition towards a multipolar international system.